2015
DOI: 10.24815/siele.v2i2.2693
|View full text |Cite
|
Sign up to set email alerts
|

Improving reading comprehension through Reciprocal Teaching Method

Abstract: This study is aimed at discovering the benefits of the Reciprocal TeachingMethod (RTM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 1 publication
2
17
0
1
Order By: Relevance
“…The students' maximum score reached 95 with the mean score 79.88. This result was in line with Komariah, et al (2015). The results showed that the students were more active and productive in the reading classroom after RTM sessions and their reading proficiency improved (Komariah, Ramadhona, & Silviyanti, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…The students' maximum score reached 95 with the mean score 79.88. This result was in line with Komariah, et al (2015). The results showed that the students were more active and productive in the reading classroom after RTM sessions and their reading proficiency improved (Komariah, Ramadhona, & Silviyanti, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Based on our initial study from informal interviews from a number of students at a junior high school in Banda Aceh, they informed that the common difficulties faced in understanding reading texts are caused by lack of vocabulary, difficult to identify main idea, understanding how to refer words in the text and detail of text. These problems were also faced by students in research previously conducted by Komariah et al (2015), Gani et al (2016), Natsir and Anisati (2016), and Yusuf et al (2016). They have used various techniques and methods to overcome these problems.…”
Section: Introductionmentioning
confidence: 99%
“…Komariah et al [24] states that the strategy in reciprocal teaching method is able to improve students' ability in understanding the content of reading. It can be seen from how the students are discussing the content of reading with other students more actively.…”
Section: Reciprocal Teachingmentioning
confidence: 99%